2008
DOI: 10.1163/156854108785787280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nematode community similarities assessed by polymerase chain reaction-denaturing gradient gel electrophoresis (DGGE) and by morphological identification

Abstract: Molecular biology techniques for nematode community analysis that are high throughput and operable by non-experts are in high demand for soil biological assessments. In the development of such techniques, the closeness of the analytical results to those obtained by conventional methods is of key importance. In this context, we compared similarity relationships of nematode community structures between polymerase chain reaction-denaturing gradient gel electrophoresis (DGGE) and individual-based morphological ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Previously, we tried to evaluate the use of PCR-DGGE for nematode community analysis, by comparing the resulting band patterns of DNA fragments with the results of morphological analyses of the nematode samples isolated from the field. We found that the correlation in similarity relationships among communities, i.e., dissimilarity matrices, between the two methods was significant, but not high (r = 0.400 0.603, Okada and Oba, 2008). One of the reasons might be that a single morphological taxon, representing a family in our study, produced two or more DNA bands.…”
Section: [Short Communication]mentioning
confidence: 56%
See 2 more Smart Citations
“…Previously, we tried to evaluate the use of PCR-DGGE for nematode community analysis, by comparing the resulting band patterns of DNA fragments with the results of morphological analyses of the nematode samples isolated from the field. We found that the correlation in similarity relationships among communities, i.e., dissimilarity matrices, between the two methods was significant, but not high (r = 0.400 0.603, Okada and Oba, 2008). One of the reasons might be that a single morphological taxon, representing a family in our study, produced two or more DNA bands.…”
Section: [Short Communication]mentioning
confidence: 56%
“…For each of these communities, we performed PCR-DGGE, as described previously (Okada and Oba, 2008;Takemoto et al, 2010). Briefly, DNA was extracted and purified from nematodes by using the Wizard SV Genomic DNA Purification System ® (Promega, Madison, WI, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acro was regarded as an internal standard against Tyl, the target. Nematode DNA samples were prepared following Okada and Oba, 6) except that 300 nematodes were used per sample. Fragments of 18S rDNA were amplified from the DNA with primers SSU9R-GC (5 0 -CGC CCG CCG CGC CCC GCG CCC GGC CCG CCG CCC CCG CCC GAG CTG GAA TTA CCG CGG CTG-3 0 ) and SSU18A (5 0 -AAA GAT TAA GCC ATG CAT G-3 0 ), originally designed by Blaxter et al 7) and modified with a GC clamp.…”
Section: )mentioning
confidence: 99%
“…PCR-DGGE was performed following Okada and Oba, 6) except that a dilution series of primer sets was used to limit PCR amplification differently. A set of reaction mixtures contained 0.6 units of Prime Star Polymerase HS (Takara, Otsu, Japan), 1Â PCR buffer, 0.2 mM dNTPs, and 0:40 Â 10 À7 ng/ml the each of the template DNAs and each of the primers at 0.096, 0.144, 0.192, 0.240, and 0.288 mM.…”
Section: )mentioning
confidence: 99%